Magnesium alloy coating with antibacterial and osteogenesis-promoting effects, preparation method and application
By preparing a magnesium alloy coating on the surface of titanium alloy, the problem of poor bacterial infection and bone integration in the repair of infectious bone defects was solved, and the dual effects of antibacterial and bone promotion were achieved, enhancing the biocompatibility and cell adhesion of the implant.
Patent Information
- Application Number
- CN202510677933.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-08-19
AI Technical Summary
Existing titanium-based implants have problems of poor bacterial infection and bone integration in the repair of infectious bone defects. Traditional surface treatment methods require two steps to prepare both antibacterial and bone-promoting capabilities, and have problems such as bacterial resistance and low load efficiency.
After treating the titanium alloy substrate with alkali, a magnesium alloy coating was prepared on the surface of the titanium alloy by RF magnetron sputtering under vacuum to form a nanoporous structure, increasing the substrate roughness and specific surface area, and combining with the RF magnetron sputtering method to prepare a uniform and dense micron-scale coating.
A magnesium alloy coating with both antibacterial and bone-promoting capabilities was achieved on the surface of titanium alloy, which enhanced the antibacterial properties and cell adhesion capabilities of the implant and promoted the osteogenesis process.
Smart Images

Figure CN120505596A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coating preparation, and in particular to a magnesium alloy coating with antibacterial and osteogenesis-promoting effects, a preparation method and an application thereof. Background Art
[0002] Titanium and its alloys, one of the most successful biomedical metals, are widely used in bone implants due to their excellent mechanical properties, corrosion resistance, and biocompatibility. However, in research on the repair of infected bone defects, titanium and its alloys exhibit good biocompatibility with bacteria on their surfaces, and their inherent chemical and biological inertness can lead to problems with bacterial infection and poor osseointegration. Therefore, when using titanium-based implants to repair infected bone defects, it is crucial to impart antibacterial and osteogenesis-promoting properties to these implants.
[0003] Surface treatment of bone implants is a common method to improve the surface properties of materials. Currently, a variety of surface treatment technologies are used to improve the performance of titanium and its alloys. Common methods include forming a bioactive coating on the surface of titanium and its alloys through technologies such as plasma spraying, electrochemical deposition and micro-arc oxidation, and then loading antibiotics, antimicrobial peptides or antimicrobial metal ions with antibacterial effects on the coating. These traditional modification methods often require two steps to prepare titanium-based implants with both antibacterial and osteogenic capabilities, and they also have to face problems such as bacterial resistance, low loading efficiency and complex preparation process. Summary of the Invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a magnesium alloy coating with antibacterial and osteogenesis-promoting effects, a preparation method and an application thereof.
[0005] The technical solution adopted by the present invention is: a method for preparing a magnesium alloy coating with antibacterial and osteopromoting effects, comprising the following steps: Step 1: treating the titanium alloy substrate with alkali, and drying the substrate to obtain an alkali-treated titanium alloy; The alkali treatment is carried out in a NaOH solution with a concentration of 4 to 6 mol / L at 60 to 70 °C for 6 to 8 hours; Step 2: The alkali-treated titanium alloy obtained in step 1 is subjected to radio frequency magnetron sputtering under vacuum conditions using Mg-0.8Ca-5Zn-1.5Ag as a target to obtain the desired magnesium alloy coating.
[0006] Furthermore, before the alkali treatment in step 1, the titanium alloy substrate is first polished, ultrasonically cleaned, and dried.
[0007] Furthermore, pre-sputtering is first performed before magnetron sputtering in step 2.
[0008] Furthermore, the pre-sputtering conditions are as follows: The pre-sputtering temperature is 200 °C, the argon flow rate is 180-200 sccm, and the sputtering time is 10-15 min.
[0009] Furthermore, the sputtering conditions are as follows: The sputtering temperature is 200 °C, the argon flow rate is 70-80 sccm, and the sputtering time is 60-90 min.
[0010] Furthermore, in the magnetron sputtering step 2, the chamber pressure is less than 0.003 Pa.
[0011] Furthermore, the ultrasonic cleaning includes the following process: Acetone, anhydrous ethanol, and deionized water were used for ultrasonic cleaning for 10 min each; The ultrasonic power is 120 W and the ultrasonic frequency is 40 KHz.
[0012] A magnesium alloy coating with antibacterial and osteogenesis-promoting effects, wherein the magnesium alloy coating has a nanoporous structure with an average pore size of 50 to 100 nm.
[0013] An application of a magnesium alloy coating with antibacterial and osteogenesis-promoting effects, wherein the magnesium alloy coating is used for preparing medical devices.
[0014] Furthermore, the medical device is a bone implant.
[0015] The beneficial effects of the present invention are: The magnesium alloy coating produced by this method first uses an alkali treatment to etch a uniformly distributed network structure onto the substrate surface. This structure increases the substrate's roughness and specific surface area, facilitating bonding between the coating and the substrate and subsequent osteoblast attachment. Using radio frequency magnetron sputtering, a Mg-0.8Ca-5Zn-1.5Ag alloy target is used to deposit a uniform, dense, micron-scale coating on the substrate surface, with a similar elemental ratio to that of the target. This coating exhibits excellent antibacterial properties and promotes osteoblast development. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a cross-sectional SEM image of the coating obtained in Example 1 of the present invention.
[0017] Figure 2 This is an SEM image of the surface of the material and the substrate material obtained in step 1 of Example 1 of the present invention.
[0018] Figure 3 Surface element analysis results of the coating obtained in Example 1 of the present invention.
[0019] Figure 4This is a schematic diagram of the results of co-culturing the material and substrate material obtained in step 1 with Staphylococcus aureus and Escherichia coli in Example 1 of the present invention.
[0020] Figure 5 This is the statistical result of CCK-8 proliferation after the material and substrate material obtained in step 1 were co-cultured with rBMSCs in Example 1 of the present invention.
[0021] Figure 6 This is a schematic diagram of the skeleton staining results after the material obtained in step 1 and the base material are co-cultured with rBMSCs in Example 1 of the present invention.
[0022] Figure 7 This is the cell spreading quantitative result of the skeleton staining result after the material and base material obtained in step 1 were co-cultured with rBMSCs in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0024] A method for preparing a magnesium alloy coating having an antibacterial and osteopromoting effect comprises the following steps: Step 1: treating the titanium alloy substrate with alkali, and drying the substrate to obtain an alkali-treated titanium alloy; First, the titanium alloy substrate was polished using 400-, 800-, and 1500-grit sandpaper, followed by ultrasonic cleaning with acetone, anhydrous ethanol, and deionized water for 10 minutes each. The ultrasonic power was 120 W and the ultrasonic frequency was 40 kHz. The substrate was then dried in a high-temperature drying oven at 60°C for 1 hour to obtain the pretreated titanium alloy substrate (βTi).
[0025] The pretreated titanium alloy substrate was placed in a 4-6 mol / L NaOH solution heated to 60-70°C and maintained at this temperature for 6-8 hours. After removal, the substrate was ultrasonically cleaned with anhydrous ethanol and then deionized water for 10 minutes each to remove any residual NaOH solution from the surface. Finally, the substrate was dried in a high-temperature drying oven at 60°C for 24 hours to obtain the alkali-treated titanium alloy βTi-A.
[0026] Step 2: Glue the alkali-treated titanium alloy substrate obtained in Step 1 to a base plate using high-temperature conductive adhesive. Mount the base plate in the designated position of the RF magnetron sputtering chamber. Lock the chamber door and begin evacuating the chamber. Once the chamber pressure drops to 0.01-0.003 Pa, turn on the heating. Once the chamber pressure reaches below 0.003 Pa and the temperature is around 200°C, introduce argon at a flow rate of 180-200 sccm and perform pre-sputtering for 10-15 minutes.
[0027] After the pre-sputtering was completed, the argon flow rate was reduced to 70-80 sccm, the baffle was lowered and magnetron sputtering began. After 60-90 minutes, the sputtering was completed, and a magnesium alloy coating (βTi-AC) with antibacterial and osteopromoting properties was obtained.
[0028] Example 1 A method for preparing a magnesium alloy coating having an antibacterial and osteopromoting effect comprises the following steps: Step 1: First, the titanium alloy substrate was polished using 400-, 800-, and 1500-grit sandpaper. Ultrasonic cleaning was then performed in acetone, anhydrous ethanol, and deionized water for 10 minutes each. The ultrasonic power was 120 W and the ultrasonic frequency was 40 kHz. The substrate was then dried in a high-temperature drying oven at 60°C for 1 hour to obtain the pretreated titanium alloy substrate (βTi).
[0029] The pretreated titanium alloy substrate was placed in a 5 mol / L NaOH solution heated to 65°C and maintained at this temperature for 7 hours. After removal, the substrate was ultrasonically cleaned with anhydrous ethanol and then deionized water for 10 minutes each to remove any residual NaOH solution from the surface. Finally, the substrate was dried in a high-temperature drying oven at 60°C for 24 hours to obtain the alkali-treated titanium alloy βTi-A.
[0030] Step 2: Glue the alkali-treated titanium alloy substrate obtained in Step 1 to a substrate using high-temperature conductive adhesive. Mount the substrate in the designated position in the RF magnetron sputtering chamber. Lock the chamber door and begin evacuating the chamber. Once the chamber pressure drops to 0.01–0.003 Pa, turn on the heating. Once the chamber pressure reaches below 0.003 Pa and the temperature is around 200°C, introduce argon at a flow rate of 190 sccm and perform pre-sputtering for 13 minutes.
[0031] After the pre-sputtering was completed, the argon flow rate was reduced to 75 sccm, the baffle was lowered and magnetron sputtering began. After 75 minutes, the sputtering was completed, and a magnesium alloy coating (βTi-AC) with antibacterial and osteopromoting properties was obtained.
[0032] Example 2 A method for preparing a magnesium alloy coating having an antibacterial and osteopromoting effect comprises the following steps: Step 1: First, the titanium alloy substrate was polished using 400-, 800-, and 1500-grit sandpaper. Ultrasonic cleaning was then performed in acetone, anhydrous ethanol, and deionized water for 10 minutes each. The ultrasonic power was 120 W and the ultrasonic frequency was 40 kHz. The substrate was then dried in a high-temperature drying oven at 60°C for 1 hour to obtain the pretreated titanium alloy substrate (βTi).
[0033] The pretreated titanium alloy substrate was placed in a 6 mol / L NaOH solution heated to 60°C and maintained at this temperature for 6 hours. After removal, the substrate was ultrasonically cleaned with anhydrous ethanol and then deionized water for 10 minutes each to remove any residual NaOH solution from the surface. Finally, the substrate was dried in a high-temperature drying oven at 60°C for 24 hours to obtain the alkali-treated titanium alloy βTi-A.
[0034] Step 2: Glue the alkali-treated titanium alloy substrate obtained in Step 1 to a base plate using high-temperature conductive adhesive. Mount the base plate in the designated position of the RF magnetron sputtering chamber. Lock the chamber door and begin evacuating the chamber. Once the chamber pressure drops to between 0.01 and 0.003 Pa, turn on the heating. Once the chamber pressure reaches below 0.003 Pa and the temperature is around 200°C, introduce argon at a flow rate of 200 sccm and perform pre-sputtering for 10 minutes.
[0035] After the pre-sputtering was completed, the argon flow rate was reduced to 70 sccm, the baffle was lowered and magnetron sputtering began. After 90 minutes, the sputtering was completed, and a magnesium alloy coating (βTi-AC) with antibacterial and osteopromoting properties was obtained.
[0036] Example 3 A method for preparing a magnesium alloy coating having an antibacterial and osteopromoting effect comprises the following steps: Step 1: First, the titanium alloy substrate was polished using 400-, 800-, and 1500-grit sandpaper. Ultrasonic cleaning was then performed in acetone, anhydrous ethanol, and deionized water for 10 minutes each. The ultrasonic power was 120 W and the ultrasonic frequency was 40 kHz. The substrate was then dried in a high-temperature drying oven at 60°C for 1 hour to obtain the pretreated titanium alloy substrate (βTi).
[0037] The pretreated titanium alloy substrate was placed in a 4 mol / L NaOH solution heated to 70°C and maintained at this temperature for 8 hours. After removal, the substrate was ultrasonically cleaned with anhydrous ethanol and then deionized water for 10 minutes each to remove any residual NaOH solution from the surface. Finally, the substrate was dried in a high-temperature drying oven at 60°C for 24 hours to obtain the alkali-treated titanium alloy βTi-A.
[0038] Step 2: Glue the alkali-treated titanium alloy substrate obtained in Step 1 to a substrate using high-temperature conductive adhesive. Mount the substrate in the designated position of the RF magnetron sputtering chamber. Lock the chamber door and begin evacuating the chamber. Once the chamber pressure drops to 0.01-0.003 Pa, turn on the heating. Once the chamber pressure reaches below 0.003 Pa and the temperature is around 200°C, introduce argon at a flow rate of 180 sccm and perform pre-sputtering for 15 minutes.
[0039] After the pre-sputtering was completed, the argon flow rate was reduced to 80 sccm, the baffle was lowered and magnetron sputtering began. After 60 minutes, the sputtering was completed, and a magnesium alloy coating (βTi-AC) with antibacterial and osteopromoting properties was obtained.
[0040] Figure 1 This is an SEM image of the cross section of the magnesium alloy coating obtained in Example 1 of the present invention. It can be seen from the image that the coating forms a uniform and dense coating on the surface of the substrate, and the coating and the substrate are well bonded, with no obvious separation at the junction.
[0041] Figure 2 The SEM images of the coating obtained in Example 1 of the present invention, the material obtained in step 1, and the surface of the substrate material show that the surface of βTi is relatively smooth and flat after gradient polishing with sandpaper of different mesh sizes; after alkali treatment (βTi-A), an irregular network structure appears on the substrate surface under the etching action of the alkaline solution, which significantly increases the surface roughness and specific surface area of the substrate; after magnetron sputtering deposition of the coating on the basis of alkali treatment, it can be seen that the surface of the coating is composed of many irregular peak-like protrusions, and there are also many tiny spherical and rod-like substances distributed on the surface of the protrusions.
[0042] Figure 3 The following are the surface elemental analysis results of the coating obtained in Example 1 of the present invention, the material obtained in Step 1, and the substrate material. The figure shows that the types of elements in the coating are roughly the same as those in the target material, and the element ratios are also basically consistent with those in the target material. This indicates that a magnesium alloy coating with the same element ratio as the target material has been successfully prepared on the substrate.
[0043] Figure 4 This is an agar plate experiment diagram of the coating obtained in Example 1 of the present invention, wherein the material and substrate material obtained in step 1 are co-cultured with Staphylococcus aureus and Escherichia coli. It can be seen from the figure that after the materials after different surface modification treatments are co-cultured with two different bacteria for a period of time, before the magnesium alloy coating is prepared by radio frequency magnetron sputtering, the number of colonies on the agar plate surface of the βTi and βTi-A groups is large, and there is no significant difference between the two groups, indicating that the alkali treatment does not change the antibacterial ability of βTi; after the magnesium alloy coating is prepared by radio frequency magnetron sputtering, the number of colonies on the agar plate surface of the βTi-AC group is significantly reduced compared with the first two groups, indicating that the magnesium alloy coating has a strong inhibitory effect on the growth of the two bacteria, that is, it has good antibacterial activity.
[0044] Figure 5The following is a schematic diagram showing the CCK-8 proliferation of rBMSCs after co-culture with the coating obtained in Example 1, the material obtained in Step 1, and the substrate material after 1, 3, and 5 days. As can be seen, the OD values of the three groups of materials continue to increase with increasing co-culture time, demonstrating that all three materials have good biocompatibility and promote cell proliferation. Furthermore, we can also observe that on day 5, the OD value of the βTi-AC group was higher than that of the βTi-A group and slightly higher than that of the βTi group, indicating that the βTi-AC group has a better ability to promote proliferation at this time point.
[0045] Figure 6 The following are skeleton staining images of the coating obtained in Example 1 of the present invention, including the material obtained in Step 1 and the substrate material, after co-culture with rBMSCs for 1, 3, and 5 days. As can be seen from the images, compared with βTi, the bone marrow mesenchymal stem cells on the surfaces of βTi-A and βTi-AC exhibited a larger spreading area and more extensive intercellular connections, and formed more abundant pseudopodia. Image J software was used to quantitatively analyze the cell spreading area of rBMSCs on day 1 after inoculation. The results are as follows: Figure 7 As shown in the figure, the βTi-AC group has the largest cell spreading area, followed by the βTi-A group, and the βTi group has the smallest. This indicates that the βTi-AC surface is more conducive to cell spreading, the magnesium alloy coating exhibits good biocompatibility with cells and has the potential to promote cell proliferation and osteogenic differentiation, creating favorable conditions for later bone formation.
[0046] The present invention first treats the substrate material with alkali, then magnetron sputtering is used to produce a magnesium alloy coating with a specific composition. The resulting nanoporous coating combines high specific surface area and stability, with an average pore size of 50 to 100 nm. This pore size facilitates coating adhesion and cell ingrowth. During the alkali treatment, excessively high NaOH concentrations, treatment temperatures, and treatment times can lead to excessive corrosion of the titanium implant surface, resulting in excessively large pores, a loose structure, and reduced mechanical strength. Excessively low NaOH concentrations, treatment temperatures, and treatment times can result in too slight etching of the titanium implant surface, preventing the formation of a continuous nanopore structure and resulting in excessively small pore sizes. Both conditions are detrimental to mechanical adhesion and cell attachment. In the present invention, a 4-6 mol / L NaOH concentration, 60-70°C, and treatment time for 6-8 hours are used to etch the titanium implant surface, resulting in a substrate structure of the desired size. RF magnetron sputtering, however, is used to produce a coating structure on an alkali-treated substrate surface. This requires both compatibility with the substrate surface structure after alkali treatment and enhanced corrosion resistance to achieve a desired coating structure. The radio frequency magnetron sputtering conditions selected in the present invention have the best performance after testing the bonding strength and corrosion rate, and can be replaced by any other preparation process conditions.
[0047] The present invention forms a coating with both antibacterial and bone-promoting components on the surface of the titanium alloy substrate through the synergistic effect of the selection of coating components and the process, thereby achieving the dual functions of antibacterial and bone-promoting. Under the combined action of the antibacterial Zn and Ag elements and the alkaline local microenvironment generated by the degradation of Mg alloy, the coating will have strong antibacterial activity. At the same time, the Mg produced by the degradation 2+ It can also promote osteogenesis by activating osteogenesis-related signaling pathways. Furthermore, the coating's microstructure facilitates the release of atoms within the coating, resulting in a coating with a specific structure that synergizes with the elements within the coating, working together to achieve a superior antibacterial and osteogenesis-promoting effect.
Claims
1. A method for preparing a magnesium alloy coating with antibacterial and osteogenic effects, characterized in that: The following steps are involved: Step 1: treating the titanium alloy substrate with alkali, and drying the substrate to obtain an alkali-treated titanium alloy; The alkali treatment is carried out in a NaOH solution with a concentration of 4 to 6 mol / L at 60 to 70 °C for 6 to 8 hours; Step 2: The alkali-treated titanium alloy obtained in step 1 is subjected to radio frequency magnetron sputtering under vacuum conditions using Mg-0.8Ca-5Zn-1.5Ag as a target to obtain the desired magnesium alloy coating.
2. The method for preparing a magnesium alloy coating with antibacterial and osteopromoting effects according to claim 1, characterized in that: Before the alkali treatment in step 1, the titanium alloy substrate is first polished, ultrasonically cleaned, and dried.
3. The method for preparing a magnesium alloy coating with antibacterial and osteopromoting effects according to claim 1, characterized in that: In the step 2, pre-sputtering is first performed before magnetron sputtering.
4. The method for preparing a magnesium alloy coating having an antibacterial and osteopromoting effect according to claim 3, characterized in that: The pre-sputtering conditions are as follows: The pre-sputtering temperature is 200 °C, the argon flow rate is 180-200 sccm, and the sputtering time is 10-15 min.
5. The method for preparing a magnesium alloy coating with antibacterial and osteopromoting effects according to claim 3, characterized in that: The sputtering conditions are as follows: The sputtering temperature is 200 °C, the argon flow rate is 70-80 sccm, and the sputtering time is 60-90 min.
6. The method for preparing a magnesium alloy coating with antibacterial and osteopromoting effects according to claim 1, characterized in that: In the step 2, the gas pressure in the magnetron sputtering chamber is less than 0.003 Pa.
7. The method for preparing a magnesium alloy coating having an antibacterial and osteopromoting effect according to claim 2, characterized in that: The ultrasonic cleaning comprises the following processes: Acetone, anhydrous ethanol, and deionized water were used for ultrasonic cleaning for 10 min each; The ultrasonic power is 120 W and the ultrasonic frequency is 40 KHz.
8. The magnesium alloy coating having antibacterial and osteogenic effects obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The magnesium alloy coating has a nanoporous structure with an average pore size of 50 to 100 nm.
9. The use of a magnesium alloy coating having an antibacterial and osteopromoting effect as claimed in claim 8, characterized in that: The magnesium alloy coating is used for preparing medical devices.
10. The use of the magnesium alloy coating with antibacterial and osteopromoting effects according to claim 9, characterized in that: The medical device is a bone implant.